Neuroinflammation in psychiatric disorders: PET imaging and promising new targets - Meyer, Jeffrey H; Cervenka, Simon; Kim, Min-Jeong; Kreisl, William C; Henter, Ioline D; Innis, Robert B (The Lancet. Psychiatry, 2020)
Neuroinflammation is a multifaceted physiological and pathophysiological response of the brain to injury and disease. Given imaging findings of 18 kDa translocator protein (TSPO) and the development of radioligands for other inflammatory targets, PET imaging of neuroinflammation is at a particularly promising stage. This Review critically evaluates PET imaging results of inflammation in psychiatric disorders, including major depressive disorder, schizophrenia and psychosis disorders, substance use, and obsessive-compulsive disorder. We also consider promising new targets that can be measured in the brain, such as monoamine oxidase B, cyclooxygenase-1 and cyclooxygenase-2, colony stimulating factor 1 receptor, and the purinergic P2X7 receptor. Thus far, the most compelling TSPO imaging results have arguably been found in major depressive disorder, for which consistent increases have been observed, and in schizophrenia and psychosis, for which patients show reduced TSPO levels. This pattern highlights the importance of validating brain biomarkers of neuroinflammation for each condition separately before moving on to patient stratification and treatment monitoring trials.